Relationship Between Dental Arch Dimensions and Bite Force: A Pilot Study - Al-Gunaid, Talat; Alrhile, Adel Suliman; Alharbi, Rayan Humaidan; Almalki, Abdullah Ahmad; Al-Gunaid, Lama Thalat; Saito, Isao (Cakradonya Dental Journal, 2024)
Objectives:This study aimstoassessthe possibleassociationbetweendental archmeasurementsandaverage and maximum bite forces.Materials andMethods:A total of 41 individuals (mean age 22.4 1.6 years) were recruitedfrom dental students and patients seekingtreatmentatthedental hospital,College of Dentistry,TaibahUniversity.Alginate impressions were taken,and study modelswerepoured,scanned,andloadedintoanalysis software for measurements. Themarkedpoints on the scanned casts were identified,andeight linear measurements were taken.Bite force wasrecordedthree timesandthe average and maximum bite forcesof the right and left sideswereobtained.The Mann-Whitney test wasutilizedto make comparisons between the right and left sides.Pearson correlation and multiple regression tests wereusedtodetecttheassociationbetween bite force and dentalarchmeasurements.Results:There was no significant differencebetween the right and left sidesbiteforces,and nosignificantrelationshipbetween themaximalanterior and posterior bite forces and mandibular arch dimensions wasfound. However, a weak correlation between the maximum bite force andmandibularintercaninewidth, arch length on the left side,andarch depth was found.Furthermore,no significantcorrelationbetween maxillary archmeasurementsand bite forcewas found. However,aweak correlation between maximum bite force andmaxillaryfirst premolar arch width, second premolar arch width, and arch length on the left side wasobserved.Conclusion:No apparent significant correlationexistsbetween the bite force and maxillary and mandibulardentalarch dimensions.Keywords:Dental Arches, Arch Dimensions, Average bite force, Maximum bite force